Estratégias pedagógicas com uso de tecnologias na formação de professores: matrizes e determinantes - Meconi Junior, Roberto (2010)
This work describes an investigative experience related to High School Math teachers Studies, more precisely about their performance in relation to the use of technologies as mediators during their classes. Through a Math Educational Didactic and technological work- shop offered in the ambit of activities in the Programa de Estudos Pós-Graduados em Educação Matemática da PUC/SP (grupo TecMEM), where a group of teachers from Estado de São Paulo Public School were under observation in the realization in dynamic activities using the software WinMat as well as in the executions of tasks with traditional medias, all of them related to the theme "matrices and determinants". Through qualitative analysis of data, it was possible to verify several difficulties by these groups of researchers, conceptual and technical, but these difficulties could decrease as soon as this articulation was being reached between the interface technological domain and the recover of mathematics concepts involved. Besides, the teachers who are in this investigation have noticed the importance of pedagogical strategies in which mathematics technological classes should be included, more than the simple use of software or other artifact to the students use